SMART SYSTEM FOR BLIND PEOPLE - Sateesh, Korapati; S., Premkumar (International Journal of Psychosocial Rehabilitation, 2020)
The articulate handle lets blind people understand and perform their work safely and quickly. With regular clamps the barrier cannot be perceived, and standard clamping for people with visual impairments is not effective. Since the blind man doesn't realize which kind of things are going before him or what sort of things are going. The person cannot see what the scale is and how far he/she is from the target. It is challenging for the blind to drive about. If the sensors sense any obstructions, the consumer is alerted by the app through the Android device. The device is particularly helpful for visually disabled individuals who sometimes require support from others. We checked and confirmed the reliability and performance of the device prototype.